Compensatory growth and feed restriction in marine shrimp production, with emphasis on biofloc technology - Maciel, Julio Cesar (2018)
In Brazil, studies and production of penaeid shrimp in a biofloc technology (BFT) system are recent, but the results point to a promising future. Research with feed restriction inducing compensatory growth in shrimps has been shown to be a technique that allows a saving of around 25% in the use of feed for shrimp production. It also allows the reduction of costs with salaries and adapts shrimp farming to the world demand for environmentally friendly production, with the reduction of nitrogen and phosphorus levels in its effluents, as well as lower water use in shrimp farming. In crustaceans, it has been shown that after a period of feed restriction, the animals show a pronounced compensatory growth when they return to a sufficient food source. Studies with the penaeid shrimp Litopenaeus vannamei reported the ability of the species to obtain a complete compensatory growth after short feeding periods (1 to 3 days) followed by feeding; These short periods of fasting presented a greater efficiency in the feed conversion besides the decrease in the concentration of phosphorus present in the aquatic environment, coming from the excreta. The adoption of a restriction program in the feeding using BFT may contribute to a reduction in operating costs, reduction of metabolic nutrients dissolved in water, and, consequently, an increase in the number of cycles in which the same water can be reused for production reducing production costs and improving productivity indices in shrimp farming.